The impact of the nocebo effect on discontinuation of statin therapy due to myopathy in patients with cardiovascular disease – a review - Jakub Stanek; Patrycja Sornek; Wiktoria Izdebska; Agata Borkowska; Radosław Ciesielski; Anna Kaźmierczak; Anna Kiełb; Anna Mich; Klaudia Perkowska; Igor Pawlak (Quality in Sport)
Introduction and purpose of review: Statins are widely used drugs in the prevention of cardiovascular diseases, yet many patients experience side effects of statin use, mainly muscle symptoms, such as myopathy, which often lead to discontinuation of treatment. The aim of this literature review is to assess the role of the nocebo effect in reported muscle symptoms and its impact on statin discontinuation in patients with cardiovascular diseases.